PEMETAAN KEARIFAN LOKAL BALI DALAM PEMBELAJARAN IPS TOPIK HARMONI DALAM EKOSISTEM PADA SISWA KELAS V SEKOLAH DASAR - Arta, I Kadek; I Wayan Lasmawan; I Wayan Kertih (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Ibn Khaldun Bogor, 2025)
This study aims to analyze Balinese local wisdom in social studies learning on the topic of Harmony in Ecosystems. This study uses a qualitative descriptive research method with a case study approach. Data collection was carried out by purposive sampling using all grade V elementary schools in the General Sudirman Cluster, Bali Province, data collection techniques were carried out by interviews, observations, and documentation. The results of the study showed that the types of local wisdom that can be inserted into social studies learning on the topic of harmony in ecosystems are: local wisdom of Tri Kaya Parisudha, Tri Hita Karana, Tumpek, and subak. The conclusion in this study is that the insertion of Balinese local wisdom in social studies learning for grade V elementary schools in the General Sudirman Cluster, Bali Province on the topic of harmony in ecosystems consists of local Tri Kaya Parisudha, Tri Hita Karana, Tumpek, and subak. Suggestions in further research can insert innovative learning models with Balinese local wisdom in social studies learning with different topics.